Ipsilateral supracondylar humerus fracture and Monteggia lesion with a 5-year follow-up: a rare injury in a young girl. (29th April 2015) - Cobanoglu, Mutlu; Şavk, Şevki Oner; Cullu, Emre; Duygun, Fatih
Abstract : Although elbow injuries and fractures of the forearm are common in children, the combination of these injuries is rare. We present a case of a 5-year-old patient with a concomitant ipsilateral supracondylar humerus fracture and Monteggia lesion. After physical and radiographic examination of the injured extremity in the emergency department, closed reduction and percutaneous pinning were performed under image intensifier under general anaesthesia. A long-arm cast was applied for postoperative immobilisation. Excellent radiological and functional outcomes were obtained at the end of 1-year follow-up and no deformity was observed at 5-year follow-up.